Articulation of The Discourse of “Islamism” As a Political Movement in Indonesia - Khoiron (MIMBAR : Jurnal Sosial dan Pembangunan, 2026)
In this article, the author describes how the discourse of "Islamism" is articulated by groups known as radical-extremists when they use discourse as a political instrument for their own interests. In Indonesia, these radical-extremist groups emerged with the opening up of public space after the New Order in 1998. On the one hand, the opening up of public space was one of the goals of reform, but on the other hand, public space became a battleground where whoever controlled public space would be the winner. The discourse of "Islamism" as a political movement is one of the discourses contested in the public sphere to reinforce the idea that Islam is not only a religion but also a political movement for the people. The political discourse of "Islamism" is a sign that radical-extremist groups are attempting to compete in the public sphere within a specific context, space, and time. In other words, the discourse of Islamism used by these entities is actually intended to legitimize the political movements they promote. In this article, the author argues that discourse is positioned as a political instrument for radical entities seeking public support, at least in the majority Muslim population. Using a literature study method, this research uncovered several findings, including a). Islam as an ideology; b). Becoming Anshorullah or defenders of God; and c). Jihad against the enemies of religion.